“中国制造”国际形象的 媒体话语研究 = International Image of “Made in China” in Media Discourse - Qiuyang, Li (Sinología hispánica. China Studies Review, 2015)
本文以《纽约时报》近二十五年对“中国 制造”报道为研究对象，从新闻话语的话语主 题、话语风格和修辞策略三个方面进行探讨， 再现了美国主流媒体对“中国制造”国际形象 的历史演变过程。研究表明，以《纽约时报》 为代表的美国主流媒介在四个历史阶段对“中 国制造”报道的主题涉及“产品标识、知识产 权、产品价格与质量、工人工作环境与待遇、 中国环境问题”等，新闻报道运用贬义词汇、 转述动词、隐喻等语言形式和话语策略，重塑 了美国大众对“中国制造”的社会认知模式。 “中国制造”的媒体形象变化与中国出口产品的 质量直接相关；美国媒体呈现的“中国制造” 产品形象与中国国家形象彼此影响。 This study aims at analyzing language forms, discursive strategies and discourse themes, focusing on the changes of international image of “Made in China” in the news reports of “New York Time” in the past 25 years. The result shows that the image of “Made in China” is constructed through methods of lexical choice, discursive stylistics, and rhetorical strategies, which is modeled under of framework of social cognition and interact with social and economic practices in daily life. The image was reflected in analyzing the theme of the relevant discourse, which covers “product symbol, copyright, product price and quality, working environment and salary of Chinese workers, and Chinese environment” and etc. These reports reconstruct the public’s social cognition towards “Made in China” by using language forms and discourse strategies contain derogatory terms, reporting verbs, and metaphors. These themes correlate with the export good quality of “Made in China”and the image of “Made in China” has a mutual impact with China image.